Direct current electric field induced gradient hydrogel actuators with rapid thermo-responsive performance as soft manipulators. Issue 8 (28th January 2020) - Mo, Kangwei; He, Meng; Cao, Xiaodong; Chang, Chunyu
Abstract : Gradient hydrogels prepared by inducing a DC-EF and in situ polymerization with thermo-responsive properties can serve as soft actuators. Abstract : Polymeric hydrogels as biomimetic soft actuators have attracted great attention, but the design of rapid responsive hydrogel actuators via a facile and sustainable pathway still faces great challenges. Herein, rapid thermo-responsive hydrogel actuators with high performances were fabricated by utilizing a direct current (DC) electric field to induce a gradient distribution of renewable tunicate cellulose nanocrystals (TCNCs) in the poly( N -isopropylacrylamide) (PNIPAM) matrix. The spatial distribution of TCNCs that acted as both nanofillers and multifunctional cross-linkers in PNIPAM was adequately demonstrated by 3D Raman technology, which played a dominant role in the fast bending (4.8° s −1 ) and recovery velocity (1.4° s −1 ) of the corresponding hydrogel actuators. Moreover, the PNIPAM/TCNC hydrogels with excellent durability and stability could be used as potential temperature-controlled manipulators for long-term capture and transportation of targeted objects, even in harsh environments.